Perhitungan Koefisien Drag dan Kooefisien Lift pada Lambung Kapal Katamaran Simetris (Symmetrical) dan Tidak Simetris (Asymmetrical) - Yunianto, Anton Hexso; Suhendra, Tonny (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2017)
Catamarans (double hull) as the river and sea transport modes that are rapidly being developed today and will likely continue to grow in the future, especially in Europe, America, and East Asia. One thing that makes popular catamaran and successfully applied in the mode of transportation because of the availability of a wide deck area, more comfortable level of stability and security. Catamarans tend to have lower water draf than the monohull vessel with the same displacement, so that it can be operated in shallow waters. Then the hull shape as a slender hull can reduce the incidence of wave wash than a single hull ship (monohull). An object moving through a fluid will experience the net force of the fluid in the body. For gastric symmetry, this force will occur in the free flow direction of a drag (D). If the stomach is not symmetrical, there will also be a normal force against the free flow of an elevator (L). Numerical modeling shows that fluid flow is laminar, critical, and turbulent. This is indicated by the direction of the vorticity field and the fluid type mass distribution, the greater the flow rate the flow properties will become increasingly random or turbulent.